(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
This article analyzes the existing approaches to understanding the concept of "effectiveness of social work"; examines the relationship between the concepts of "effect", "effectiveness", "efficiency"; showing some generalizations existing classification criteria for evaluating the effectiveness of social work and social policy implementation, which in turn will explore the theory and practice of social work in Spadschini Mary Ellen Richmond.